From Preschool to Prison: How School Resource Officers Produce Criminality - Vargas Tapia, Brenda (2021)
Police officers were introduced in the American school system to provide White communities with a sense of safety. However, these police officers are not well trained to provide students with support and instead are trained to deal with situations with force. The implicit bias of police officers criminalizes and punishes Black, Indigenous, and People of Color (BIPOC) students unfairly. School shootings have continued to enforce the idea that officers are needed. However, this notion is untrue. Policing in schools builds a school-to-prison pipeline that is now, in the online schooling era, translating to the Zoom-to-prison pipeline, which reveals that BIPOC youth live in a carceral state where they do not need physical school buildings to be castigated. The case study of San Jose emphasizes the need to invest in BIPOC rather than invest in School Resource Officers (SROs). Schools across the nation must cease their SRO program contracts with their local police department and invest in much-needed resources instead. People with privilege must step up and work towards dismantling the structures and racist ideologies that fuel the injustices towards BIPOC youth in schools. Investing in other resources, such as mental health resources, will cultivate a healthy school environment, removing the need for police officers. Current harmful injustices must be abolished in order to change the structure of education and provide a joyful and rigorous education to BIPOC youth